Relevance of temperament traits in sexual fluidity in a sample of Spanish young university students - Negredo, Adelia De Miguel (Advances in Social Sciences Research Journal, 2020)
Assessing the relevance of temperament traits to predict sexual fluidity, taking into account gender and sexual orientation, was the main goal of this paper. Participants (435 Spanish young-adults students, 310 females and 125 males) completed an online questionnaire, which included measures of sexual fluidity, the short version of the Big Five Inventory, two factors of Sensation Seeking Scale, and State-Trait Anxiety Inventory. Analyses showed gender differences in sexual fluidity, anxiety and sensation seeking. Sexually fluid individuals also reported higher scores than no-sexually fluid individuals in these factors. Bisexual orientation, anxiety-trait and sensation seeking were good predictors of female sexual fluidity. Anxiety state was relevant to male sexual fluidity. We concluded that sexual fluidity can be related to emotional and biological personality traits, but it is not clear if the origin of this relationship is only biologically caused or depends on experience moderator effects. Again, the controversy nature-nurture is needed to be considered when assessing sexual fluidity across life-span.